Estudos para o desenvolvimento de uma metodologia de definição de teores deletérios de enxofre em concretos e argamassas de barragens - Ana Paula Borges Marcelino (2015)
It is well known that aggregate characteristics can intensively interfere in concrete behavior especially when sulfides are presented in the aggregates. The lack of consensus to content limit value of these deleterious sulfur compounds in concrete structures for dams has motivated several investigations worldwide. Within this scenario, this work presents a study for the development of a methodology to target sulfur component levels in concretes, which will may lead to set maximum values to be used in hydroelectric dams. For the study, rock samples from the Irapé hydropower plant area in Minas Gerais (Brazil) were used. This plant was built in a geological site where the rock presented sulfide levels of at least 3%. These rock samples were first grinded and then used as aggregates in mortars which were subjected to three different exposed conditions: temperature of 23° ± 2°C and relative humidity of 95 to 100%; calcium hydroxide solution diluted in water kept at two different temperatures: room temperature and 50° C± 2°C. The expansion values and splitting tensile strength of the mortars as well as the sulfur compound contents, predominant on the rocks (pyrite and pyrrhotite), were the main parameters used for mortar behavior evaluation over time. The amounts of sulfides were obtained from a leaching process of the material (aggregate and mortar). Hydrochloric acid solution was used to dissolve pyrrhotite, which allowed the quantification of remaining pyrite content. The amount of pyrrhotite was determined by the difference between the initial amount of sulfur and the amount of the sample after this leaching procedure. The results obtained showed that the pyrite content remained practically constant over the period of time independently of the three exposure situations, This fact suggests that sulfur limits in aggregate should be prescribed according to the type of this iron sulfide, not only the total quantity of sulfur.